2019
DOI: 10.3389/fped.2019.00311
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mycobacterium tuberculosis Infection in Infants and Children With Partial Discrimination Between Active Disease and Asymptomatic Infection

Abstract: Background: Improved diagnostic tests are needed for the early identification of Mycobacterium tuberculosis- infected young children exposed to an active TB (aTB) index case. We aimed to compare the diagnostic accuracy of new blood-based tests to that of the tuberculin skin test (TST) for the identification of all infected children and for a potential differentiation between aTB and latent TB infection (LTBI). Methods: 144 children exposed to a patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Samples from a second, independent cohort of children were tested afterwards, representing a validation cohort. This cohort comprised 60 children included in a study evaluating the ability of antigen-induced blast cells as determined by flow cytometry, to identify and correctly classify M. tuberculosis -infected children ( 13 ). This was a whole blood assay, and an IGRA in response to mycobacterial antigens was performed in parallel on PBMC ( 14 , 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…Samples from a second, independent cohort of children were tested afterwards, representing a validation cohort. This cohort comprised 60 children included in a study evaluating the ability of antigen-induced blast cells as determined by flow cytometry, to identify and correctly classify M. tuberculosis -infected children ( 13 ). This was a whole blood assay, and an IGRA in response to mycobacterial antigens was performed in parallel on PBMC ( 14 , 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…Flowcytometric acquisition of PT-specific lymphocytes PT-specific lymphocytes (CD3 + , CD3 + CD4 + and CD3 + CD8 + blasts) were measured on heparin blood samples using a specialized Flowcytometric Assay that detects the Specific Cellmediated Immune response in Activated whole blood (FASCIA). Based on previous protocols [16][17][18] whole blood was diluted 1/10 in RPMI 1640 (Life technologies) supplemented with 50 μg/mL gentamycine, 2 mM L-glutamine, MEM non-essential AA, Na pyruvate, 2Bmercapthoethanol and Fetal Bovine Serum. Diluted blood was either left unstimulated (negative control) or stimulated with 5 μg/mL PT antigen (heat-inactivated PT, Bordetella pertussis strain 165, List Biological) or 1 μg/mL Staphylococcal enterotoxin B (SEB, positive control).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…TB can be asymptomatic or latent, resulting in a delay in diagnosis, and, in 2019, an estimated 10 million people fell ill with the disease. This delay in diagnosis is compounded by the increasing prevalence of variants of Mycobacterium tuberculosis resistant to rifampicin, the first-line drug of choice for TB treatment. , The sequencing of the whole genome of Mycobacterium tuberculosis revealed that 95–98% of all rifampicin-resistant strains is related to single-nucleotide polymorphisms (SNPs), located in the 81 bp RIF-resistance determining region (RRDR) of the beta subunit of the RNA polymerase (rpoB) gene. The World Health Organization reported that around half a million people developed rifampicin-resistant TB in 2019, and in 2010, recommended the use of the Xpert MTB/RIF assay (Cepheid, Sunnyvale, CA) for the detection of TB and rifampicin resistance, and while it is widely used, its implementation in developing countries is hampered by many issues, including cost, maintenance, and power requirements.…”
mentioning
confidence: 99%